Necesidad de reformar la ley orgánica de servicio público respecto a la estabilidad en los contratos de servicios ocasionales - Hidalgo Pasaca, Carlos Roberto (2015)
This is a labor law issue of singular importance to humans and be at stake the foundation of the state is the family and their livelihood is economic, the mode of occasional contract by its nature doesn’t create stability and therefore it has been determined that generates distress in families that depend on a worker with such a contract. Therefore, it was necessary to put on the table legal situations of this kind that helped them widely and to provide adequate scientific looking to solve problems such as "the impact of occasional contract for stability in contracts for occasional services" contributions form The goals were vital when a critical, reflective, doctrinal and legal study of the problem, allowing together with the appropriate methodology to collect information and propose a draft amendment to the last paragraph of Art. 58 of the Organic Law Public Service relative to repeal the limitation to the renewal of contracts for occasional services, which creates legal uncertainty and contradiction with the supreme law of the Constitution of the Ecuador Republic, violating the workers’ rights